Influence of Polyphenol Extract from Evening Primrose (Oenothera Paradoxa) Seeds on Proliferation of Caco-2 Cells and on Expression, Synthesis and Activity of Matrix Metalloproteinases and Their Inhibitors - Szewczyk Karolina; Lewandowska Urszula; Owczarek Katarzyna; Sosnowska Dorota; Gorlach Sylwia; Koziołkiewicz Maria; Hrabec Zbigniew; Hrabec Elżbieta (Polish Journal of Food and Nutrition Sciences)
Evening primrose (Oenothera paradoxa Hudziok) seeds are a rich source of not only a valuable oil containing an essential fatty acid - ᵧ-linolenic acid (GLA) - but also polyphenols which can be obtained from the biomass remaining after oil pressing. The aim of our studies was to evaluate the influence of a polyphenol extract from defatted seeds of evening primrose on human colorectal adenocarcinoma Caco-2 cell proliferation and matrix metalloproteinases (MMPs) synthesis and activity. To assess the effect of evening primrose extract on Caco-2 cell proliferation, crystal violet staining and sulforhodamine B (SRB) assays were used whereas mRNA expression and activity of MMPs were evaluated by RT-PCR and gelatin zymography.